Auricular and periauricular melanomas have similar clinicopathologic factors and survival rates. (18th June 2021) - Tas, Faruk; Erturk, Kayhan; Ferhatoglu, Ferhat
Abstract: Background: Auricular melanomas are rare malignancies, and conflicting reports regarding their clinical behaviors have been published so far. Objective: In this study, we investigated the clinical features of the auricular melanomas and compared them with periauricular skin melanomas. Methods: Data of 53 primary melanomas arising in auricular ( n  = 25) and periauricular regions ( n  = 28) were analyzed retrospectively. Results: Demographic, histopathological, and clinical characteristics were found similar between auricular and periauricular melanomas ( p  > 0.05). Likewise, the recurrence rates for both groups were found to be similar (30%) ( p  = 0.9). The 5‐year relapse‐free survival rate of all patients was 57.4%, and no statistical difference was observed between the two groups—63.9% for auricular melanomas and 51.7% for periauricular melanomas ( p  = 0.5). Moreover, the 5‐year overall survival rate of all melanomas was 46.9%, and there was no statistical significance between the two groups—56.1% and 37.4% for auricular and periauricular melanomas, respectively ( p  = 0.4). Conclusion: Auricular and periauricular melanomas share similar clinicopathologic features and outcomes.